Improving Poetry Writing Ability Using Acrostic Technique in Class X Students of Vocational School Taman Karya Madya Pertambangan Kebumen - Patria Endah Safitri (NOTION: Journal of Linguistics, Literature, and Culture, 2020)
This study aimed to describe: 1) the process of learning to write poetry using the acrostic technique, 2) students' interest in learning to write poetry using the acrostic technique, and 3) improvement of the ability to write poetry using the acrostic technique in class X students of SMK Taman Karya Madya Pertambangan Kebumen. This research is classroom action research that consists of three stages of research, namely pre-cycle, cycle I, and cycle II. The instruments used were test and note instruments. Data analysis techniques in this study used quantitative and qualitative techniques. The results of this study were in the form of learning steps for the ability to write poetry in class X students of SMK Taman Karya Madya Pertambangan Kebumen using acrostic techniques, namely (a) the teacher explained the meaning of poetry and the building elements of poetry, (b) the teacher explained the material for writing poetry using techniques acrostic, (c) the teacher gave examples of poetry using the acrostic technique, (d) the teacher and students conducted questions and answers about writing poetry using the acrostic technique, (e) the teacher gave assignments to students to compose poetry using the acrostic technique, and (f) students collected results of writing poetry with the acrostic technique to the teacher. The effect of the acrostic technique on students' interest in learning can be seen in the pre-cycle of 29.41%, cycle of 58.82%, and cycle II of 88.23%. The increase in the ability to write poetry results can be seen from the average value, namely, 63.82 in the pre-cycle, increasing to 73.24 in the first and 80.88 in the second cycles.